Expenditure on Human Capital and Economic Growth: Evidences form Nepal - Khanal, Santosh (Tribhuvan Journal, 2023)
Human capital expenditure is critical to utilizing and profiting from all of the country's resources. Economists have acknowledged that human capital improvement and usage are critical to a nation's economic prosperity. The research article investigates the relationship between human capital spending and Nepal's economic growth. The study analyzed data from 1985 to 2022 to investigate experimentally the relationship between Nepal's human capital spending and GDP. The study uses a variety of macroeconomic indicators, such as GDP as a measure of economic growth, capital expenditure on education, recurrent expenditure on education, health expenditure, higher education enrollment, and school enrollment. LNRGDP serves as both the explanatory variable and the dependent variable in the study's use of regression analysis. The Unit Root Test, OLS Estimation, Unit Root Residual and Error Correction Approach, and Econometric Analysis are all included. The results of the regression show that higher enrollment has a positive effect while capital expenditure on education has a negative impact on GDP. Spending on ongoing education, health, and school enrollment has no statistically significant effect on GDP. A long-term, positive correlation between the investment in human capital and economic growth is found by the cointegration test. According to the findings, funding higher education is essential for fostering Nepal's economy. In addition, the study highlights the significance of policymakers carefully considering resource allocation for education and human capital development in order to ensure the nation's sustainable growth